Drug safety evaluation - Gad, Shayne C., 1948-; Sullivan, Dexter W., Jr (John Wiley & Sons, Inc., 2023)
"This new edition of Drug Safety Evaluation presents an all-inclusive practical guide for those who are responsible for developing new drugs and ensuring the safety of an ever-expanding spectrum of therapeutics. This book helps readers understand how the safety of these products are evaluated for use. Extensively revised to reflect up-to-date information, this edition includes changes to the scope of products (vaccines, small synthetic, large protein moieties, cells and tissues), harmonized global and national regulatory requirements, the therapeutic development process, and available technologies to identify and evaluate the relevance of potential patient risks. The revised chapter, and inclusion of brand-new chapters, address specific approaches to evaluating hazards, including problems that are encountered and their solutions. Also covered are the scientific and philosophical bases for evaluation of specific concerns (including carcinogenicity, developmental toxicity, immunogenicity and immunotoxicity) to provide both understanding and guidance for approaching new problems"--